Sorting out the standards: what every records and information professional should know - Pember, Margaret (Emerald Group Publishing Limited, 2006)
Purpose: The purpose of this article is to explore the types of standards that exist for records and information management and examples of their use in practice. Design/methodology/approach: The article is based on literature and the author's own knowledge. Findings: Finds that standards provide a reference point for measurement, a global best practice benchmark against which to evaluate any record-keeping program. Originality/value: This article explores the types of standards that exist and examples of their use within records and information management. An overview of the value of standards as an essential tool of RIM practice is provided.